1988
DOI: 10.1002/jmor.1051970204
|View full text |Cite
|
Sign up to set email alerts
|

Muscular mechanisms of snake locomotion: An electromyographic study of lateral undulation of the florida banded water snake (Nerodia fasciata) and the yellow rat snake (Elaphe obsoleta)

Abstract: Electromyography and cinematography were used to determine the activity of epaxial muscles of colubrid snakes during terrestrial and aquatic lateral undulatory locomotion. In both types of lateral undulation, at a given longitudinal position, segments of three muscles (Mm. semispinalis-spinalis, longissimus dorsi, and iliocostalis) usually show synchronous activity. Muscle activity propagates posteriorly and generally is unilateral. With each muscle, large numbers of adjacent segments (30 to 100) show simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 11 publications
7
134
0
Order By: Relevance
“…On flat surfaces the weight of the convoluted region of the snake appears sufficient to create an anchoring region (Gray, 1946), whereas all other forms of concertina movement probably involve actively pressing the body against surfaces to attain an anchoring region or grip. Electromyograms of snakes performing concertina locomotion in tunnels are consistent with the snakes pressing outward against the vertical sides of tunnels (Jayne, 1988b), whereas moving on cylinders probably requires pressing inward to establish a grip.…”
Section: Modes Of Locomotionmentioning
confidence: 60%
See 1 more Smart Citation
“…On flat surfaces the weight of the convoluted region of the snake appears sufficient to create an anchoring region (Gray, 1946), whereas all other forms of concertina movement probably involve actively pressing the body against surfaces to attain an anchoring region or grip. Electromyograms of snakes performing concertina locomotion in tunnels are consistent with the snakes pressing outward against the vertical sides of tunnels (Jayne, 1988b), whereas moving on cylinders probably requires pressing inward to establish a grip.…”
Section: Modes Of Locomotionmentioning
confidence: 60%
“…For example, a recent analysis of force platform data found that some tetrapods with walking and running kinematics (duty factors <50% and >50%, respectively) actually had running or walking mechanics (Reilly et al, 2006). Similarly, aquatic and terrestrial lateral undulation of snakes have continuous posterior propagation of lateral bending but different phase relationships between bending and muscle activity (Jayne, 1988a).…”
Section: Modes Of Locomotionmentioning
confidence: 99%
“…The use of epaxial musculature for bending in the sandfish resembles the case in other taxa [e.g. amphibians (Frolich and Biewener, 1992) and snakes (Jayne, 1988)] that use epaxial muscle for lateral bending. There is some evidence that epaxial muscle may be used during high-speed (>3SVL s −1…”
Section: Discussion the Role Of Epaxial Musculature In Lateral Undulamentioning
confidence: 89%
“…Studies have shown that for elongate animals with uniform body shape, such as the eel (Gillis, 1998a) and lamprey (Williams et al, 1989;Wardle et al, 1995), EMG duration changes are small along the length of the body compared with those in fish with differing body diameter and shape (Wardle et al, 1995;Altringham and Ellerby, 1999). Also, the duty cycle in sandfish was comparable to that in other animals such as the terrestrial snake [~0.45 in iliocostalis of Nerodia fasciata) (Jayne, 1988)] and aquatic lamprey [~0.5 (Williams et al, 1989)], despite differences in environment. Currently, we do not understand what factors influence this timing and how the environment might play a role.…”
Section: Activation Timing During Subsurface Swimmingmentioning
confidence: 99%
“…This constancy of  bend with variable Gap max suggests  bend may be the primary limiting factor for performance over a wide range of conditions. Such a limit may result from the maximum muscular force that can be exerted (Jayne and Riley, 2007) by the semispinalis-spinalis (SSP) and multifidus (M) muscles, which are the primary dorsal flexors in snakes (Jayne, 1988). Three observations suggest that  pitch does not play a dominant role in determining maximum performance: (1) for orientations where torques were greatest, 50% or more of the total length of the body remained on the supporting perch to act as a counterweight, (2) snakes used their body or tail to wrap the perch or pegs, offsetting any tendency to pitch, and (3) all observed failures were the result of localized bending of the body rather than rigid-body pitching off the end of the perch.…”
Section: Limits To Gap-bridging Performancementioning
confidence: 99%